Wanita Dalam Gejala Tidak Bermoral Dan Kaedah Membina Kesejahteraan Hidup (Sains Humanika, 2018)
This research is discusses about the involvement of a handful of women immoral activities such as beggars, homeless, drug addicts, sex workers, pregnan before marriage in Kuala Lumpur City. This situation affects the image of the capital in the eyes of tourists, problems urban sanitary issues and publicly exposed to infectious diseases. Increased crime, security issues, urban hygiene and social health are rising due to various factors. The objective of the study is to identify women being involved in illegal activities and the methods of building a good rules in lives. This method is uses library research and field study. Field studies include interviews and observations. Focus location of study is Kuala Lumpur City as "hotspots area" the public area. Three women respondents was selected in this study. This findings is that normally involved women immoral activities come from unhappy family backgrounds, low levels of education and engagement in jobs of lucrative income. Another problem is not enough finance for respondents, homeless survivors, family conflict and understanding about Islam is very low. The proposal to rebuild the new life of the women involved in the immoral activities returned to the community is to approach them with wisdom, providing temporary shelter, learn basic Islamic teachings, helping financial resources such zakat and to give skill training which suits their ability.
Keywords: Social problems; immoral activities; women; causes; guidance; prosperity.